Innova Technology (B): Growing the business for anti-loss devices - NARASIMHALU, Arcot Desai (Institutional Knowledge at Singapore Management University, 2013)
This case is the second part of a two-part series on Innova Technology, a technology start-up company based in Singapore. The two cases focus on: Case (A) – Developing, producing and marketing a product innovation Case (B) – Growth strategies and its related challenges for a young technology company The case is set in November 2012, two months after the launch of PROTAG, a new anti-loss device developed by Rick Tan and his partner, Jonathan Lim. Tan is the chief executive officer of Innova Technology Private Limited, the company that manufactures and sells PROTAG. After a highly successful product launch, Tan is contemplating his company’s growth strategy. Tan and his business partner, Jonathan Lim, who is also the Chief Technology Officer for Innova Technology, developed PROTAG, a new anti-loss device, using Bluetooth technology. The device, which is about the size of two credit cards stacked together, is synched to a mobile phone and can be attached to valuable personal belongings such as keys, wallets, handbags, passports and even phones. If the valuable item were to be separated from the person by more than a certain distance, the device would set off an alarm alerting the owner of its potential loss. After extensive market research and encouraging results from beta test sales using the crowdfunding site Indiegogo, Tan was confident of his product. He executed a well-thought out marketing plan which targeted customers in the travel segment. Despite the high commissions charged by distributors, Tan decided to use this channel to market his product. He negotiated with Sprint-Cass Pte Ltd, a specialised supplier to travel retail and duty free channels which had presence in Asia and the Middle East. The first 5,000 devices were sold within two months and Tan had to place new rush orders for manufacturing to keep up with the demand. The team was celebrating – in less than two years; Innova Technology had successfully made its foray into the market for anti-loss devices and established a niche customer base. Yet Tan couldn’t help but ponder about his company’s growth strategy. He once again found himself at crossroads. What would his company’s next steps be? Should there be a PROTAG Gen II? Should he consider expanding globally? Did his company have the capacity, capabilities and skill set to take their product beyond Singapore and Asia? How else could he grow his business?